Prosociality and Risk: How Risky Decision-Making in Young Adults Relates to Altruistic Tendencies, Empathic Concern, and Prosocial Peer Affiliation - Beard, Sarah J (2017)
Adolescence involves an increase in risky decisions, such as reckless driving and illicit substance use, but prosocial characteristics and peer affiliation have yet to be investigated as protective factors. The present study assessed altruistic tendencies, prosocial peer affiliation (PPA), and empathic concern as predictors and moderators of risk-taking, including both self-reported health risks and riskiness in a behavioral task. Young adults from ages 20 to 25 (M = 22.55, SD = 1.38) completed a battery of behavioral tasks (including the Balloon Analogue Risk Task and the Dictator Game) and questionnaires on Amazon MTurk, measuring risk-taking (drunk driving, texting while driving, binge drinking, illicit substance use, and tobacco use), altruistic tendencies, PPA, empathic concern, reward sensitivity, and self-regulation. Results indicated that drunk driving and texting while driving were negatively associated with all three prosocial characteristics, and binge drinking was related to PPA and empathic concern. Moderating effects included interactions between altruistic tendencies and reward sensitivity on drunk driving, altruistic tendencies and self-regulation on drunk driving, PPA and reward sensitivity on binge drinking, and empathic concern and self-regulation on binge drinking. Mediating effects, however, were not found. Overall, prosocial characteristics seemed to buffer against reward sensitivity and strengthen self-regulation in several models. The discussion centers on how prosocial individuals might be less prone to risk-taking, and how affiliating with positive peers can offset the effects of heightened reward sensitivity during this crucial developmental period